Comparative Effects of Therapeutic Massage and Acupressure on Neck Pain: Therapeutic Massage and Acupressure in Neck Pain - Mengal, Saba; Memon, Aamir Gul; Chaudhary, Fatima; Shah, Saleh; Afzal, Muhammad Faheem; Sanaullah, Muhammad; Nawaz, Sumaira; Abdul Latif, Falak (Pakistan BioMedical Journal, 2022)
Depending on the cause, neck pain can persist anywhere from a few days to several years; Osteoarthritis, spinal stenosis, ruptured disc, pinched nerves, emotional and physical stress, strain, bad posture, tumor, and other disorders are among the most common causes acupressure on local and distal acupuncture sites may provide drowsiness and relaxation, which may help to relieve chronic neck discomfort. Objective: To compare the effects of therapeutic massage and acupressure on neck pain. Methods: ISRA University Hospital Karachi conducted a randomized clinical trial. A total of n=30 individuals were between the ages of 20 and 35, with neck discomfort ranging from 3-6 on the VAS scale. The n=30 participants were separated into two groups: therapeutic massage (n=14) and acupressure (n=15). The data was analyzed using the SPSS version 22.0. Results: Mean age of study participants was 24.34± 4.3 years. A total of n=12 were female, and the remaining n=18 were male. The analysis showed that pain and neck disability significantly improved in both groups (p<0.05). When compared in both groups, the intensity of pain was not significantly different in both groups, but neck disability was significantly improved in the acupressure group as compared to the massage group after six weeks of intervention. Conclusion: The study concluded that both techniques benefit neck pain and disability and found significant results. But results show that acupressure was found to be more beneficial and significant than the therapeutic massage.